2-cyclohexylamino-5, 8-dimethoxy-1, 4-naphthoquinone inhibits LPS-induced BV2 microglial activation through MAPK/NF-kB signaling pathways. Issue 7 (July 2016) - Sun, Hu-Nan; Shen, Gui-Nan; Jin, Yong-Zhe; Jin, Yu; Han, Ying-Hao; Feng, Li; Liu, Lei; Jin, Mei-Hua; Luo, Ying-Hua; Kwon, Tea-Ho; Cui, Yu-Dong; Jin, Cheng-Hao
Abstract: Aims: To verify the effects of several 5, 8-dimethoxy-1, 4-naphthoquinone (DMNQ) derivatives on LPS-induced NO production, cellular ROS levels and cytokine expression in BV-2 microglial cells. Main methods: An MTT assay and FACS flow cytometry were performed to assess the cellular viability and apoptosis and cellular ROS levels, respectively. To examine the expression of pro-inflammatory cytokines and cellular signaling pathways, semi-quantitative RT-PCR and Western blotting were also used in this study. Key findings: Among the six newly synthesized DMNQ derivatives, 2-cyclohexylamino-5, 8-dimethoxy-1, 4-naphthoquinone (R6) significantly inhibited the NO production, cellular ROS levels and the cytokines expression in BV-2 microglial cells, which stimulated by LPS. Signaling study showed that compound R6 treatment also significantly down-regulated the LPS-induced phosphorylation of MAPKs (ERK, JNK and p38) and decreased the degradation of IκB-α in BV2 microglial cells. Significance: Our findings demonstrate that our newly synthesized compound derived from DMNQ, 2-cyclohexylamino-5, 8-dimethoxy-1, 4-naphthoquinone (R6), might be a therapeutic agent for the treatment of glia-mediated neuroinflammatory diseases.